Memory and Identity Politics in the European Union: Related Concepts, Disparate Practices - L. A. Fadeeva (Международная аналитика, 2022)
The author characterizes memory politics and identity politics as analytical categories formed in a highly competitive field of meanings and interpretations. The methodological approach is social constructivism, which represents the mainstream in the study of memory and identity politics. However, the author considers it necessary to take into account the socio-cultural framework of actions performed by various actors that shape memory and identity. In addition, sharing the methodologically innovative approach advanced by I.S. Semenenko to the definition and analysis of identity politics, the author applies it to the object of her research. The article proposes using the concept of securitization to study not only the politics of memory, but also the identity politics pursued by the European Union. The shaping of a European identity on the basis of memory politics involves many problems, both supranational and national. This article deals primarily with supranational policy, but national discourses of memory and identity politics are also taken into account. In this context, the concepts per se, which have categorical conjugacy, turn out to be associated with courses characterized by considerable discord. The seemingly unshakable foundations of memory politics, established after World War II, are being challenged by the new member states of the European Union, shaping different practices of remembrance and forgetting. As a result, implying the possibility of different interpretations and harmonization of discourses, dialogical memory as the foundation of European identity is giving way to the securitization of memory politics and identity politics, which means their instrumental use to legitimize specific policies.